Keputusan Petani Menjadi Penangkar Benih Padi di Kabupaten Purworejo - Ari Restu Aji; Didik Widiyantono; Arta Kusumaningrum (Jurnal Riset Agribisnis dan Peternakan, 2019)
The objectives of the study were to 1) determine the characteristics of rice seed breeder farmers in Purworejo Regency, 2) determine the relationship between internal and external factors with farmers 'decisions in conducting rice seed breeder farming, 3) determine the internal and external factors that influence farmers' decisions in conducting seed breeding farming rice. The sampling of the study area was determined based on purposive sampling. The chosen location is Purworejo Regency. Samples taken in the village of Awu Awu were 13 people, in Sukomanah village were 10 people, in Seborokrapyak village were 6 people, in Lugu village were 3 people, in Tunjungrejo village were 6 people. Determination of the number of samples based on a Likert scale. The instrument used in this study was a questionnaire. The results showed that 1) formal education, availability of facilities and infrastructure, partnership support had a strong relationship with farmers 'decisions, while suitability with land aspects and ease of effort had a very strong relationship to farmers' decisions inbreeding seed farming, 2) partnership support had a significant influence on farmers' decisions.